2016
DOI: 10.1080/03007995.2016.1203767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two anatomic landmarks using ultrasonography in spinal anesthesia: a randomized controlled trial

Abstract: We conclude that the tenth rib line is better than Tuffier's line for accuracy with palpation. However, it must be confirmed by further studies including more than one examiner for palpation and also include different patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…In the present study, the accuracy of Tuffier line was 59%, consistent with previous studies showing its accuracy of 60% to 64% in general population. [7,9] The accuracy of the 10th rib line was 57%, which was lower than the result in a previous study where showed the 74% accuracy of the 10th rib line. [7] In that study, they compared Tuffier line and the 10th rib line to predict the L4-L5 intervertebral space in young and healthy population, and showed that the 10th rib line is more accurate than Tuffier line (74% vs 60%, respectively).…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…In the present study, the accuracy of Tuffier line was 59%, consistent with previous studies showing its accuracy of 60% to 64% in general population. [7,9] The accuracy of the 10th rib line was 57%, which was lower than the result in a previous study where showed the 74% accuracy of the 10th rib line. [7] In that study, they compared Tuffier line and the 10th rib line to predict the L4-L5 intervertebral space in young and healthy population, and showed that the 10th rib line is more accurate than Tuffier line (74% vs 60%, respectively).…”
Section: Discussioncontrasting
confidence: 70%
“…[7,9] The accuracy of the 10th rib line was 57%, which was lower than the result in a previous study where showed the 74% accuracy of the 10th rib line. [7] In that study, they compared Tuffier line and the 10th rib line to predict the L4-L5 intervertebral space in young and healthy population, and showed that the 10th rib line is more accurate than Tuffier line (74% vs 60%, respectively). With the 10th rib line, the L4-L5 intervertebral space is determined by counting down the level from the 10th rib line that corresponds to the L1-L2 intervertebral space or the body of L2.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations